Gynecologic Conditions in a Cohort with Inflammatory Bowel Disease: A Descriptive Analysis - Díaz-Mayor, Diego J.; Soto-González, Alondra; Alicea, Kileisha G.; Núñez-González, Stephanie; Merheb, Pamela A.; Vázquez, Kimberly; Torres, Esther A.; Romaguera, Josefina (Puerto Rico Health Sciences Journal, 2023)
Objective: Past studies have demonstrated that women with inflammatory bowel disease (IBD) have a higher risk of gynecological conditions than do women without it. We aimed to characterize the gynecological histories of Hispanic Women living in Puerto Rico with IBD. Methods: We identified women, aged 21 to 55 years, with a confirmed IBD diagnosis and receiving follow-up care from the University of Puerto Rico IBD clinics from 2017 through 2020. A questionnaire was administered to acquire sociodemographics, family history, past medical history, IBD diagnosis, and gynecologic aspects. Results: One hundred eighty-six women were recruited. Fifty-three (28%) patients had ulcerative colitis, while 133 (72%) had Crohn’s disease. Fifty-six percent of all the participants had a chronic illness in addition to than their IBD. Seventy-four out of 186 patients reported having had at least 1 late period within the last 12 months. Fifty-three (28%) described their period patterns as irregular. Thirty-nine (21%) of the patients reported having been vaccinated against human papillomavirus (HPV), and 8 (4%) had been infected by it. Nine out of 186 (5%) patients reported suffering from infertility. Conclusion: The results showed that our Hispanic patients (living in Puerto Rico) had a prevalence of irregular menstrual cycles that was similar to that observed in other populations. On the other hand, the presence of HPV, infertility, and cervical cancer were lower and the frequency of Papanicolaou smears performed higher than what has been seen in the continental United States, suggesting that this topic should be investigated in future studies.